The public realm during public health emergencies: exploring local level responses to the COVID-19 pandemic. (21st July 2021) - Wray, Alexander; Fleming, John; Gilliland, Jason
ABSTRACT: The public realm is a well-recognized contributor to positive health and wellbeing. Public parks and recreational spaces are now some of the main outlets for people to get outdoors, however COVID-19 has created challenges in these spaces. We classify local government responses around maintaining physical distancing in the public realm using a preliminary conceptual map of theories and actions to identify variations in these approaches around the globe. This pilot classification approach provides a useful lens to examine pandemic responses, with future work building upon this map to potentially inform how cities may react to other complex planetary health issues.